ASUHAN KEBIDANAN PADA IBU R DENGAN METODE PERSALINAN TIUP TIUP UNTUK MENCEGAH ROBEKAN JALAN LAHIR - karmila, Aja; Julianti, Rina; Yushida, Yushida; Asmanidar, Asmanidar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Introduction: . MMR has fallen by around 34% worldwide. An estimated 287,000 women lost their lives from mostly preventable causes of pregnancy and childbirth-related diseases in 2020, around 800 women every day or equivalent to 223 deaths per 100,000 Live Births (LBR). The Southeast Asia Region maintained the fastest rate of reduction during the MDG era and the first five years of the SDG era, reducing the maternal mortality ratio from 372 deaths per 100,000 LBR in 2000 to 117 deaths per 100,000 LBR in 2020. Objective: This study was to provide midwifery care to Mrs. R to reduce tearing of the birth canal experienced by the mother in labor. Research Method: The design of this care was in the form of a case study with a qualitative approach. This study provides care for the Subject of this case study is mother R aged 38 years G3P2A0, at 38 weeks of pregnancy, the mother wants to give birth in West Aceh district. This study was conducted on March 14-03, 2025. Results: The results of the study obtained that after being given care, the mother felt calm when applying the blow-blowing delivery method. Conclusion: Midwifery care with the blow-blowing delivery method during labor has proven that there is no tearing of the birth canal when the mother is giving birth.